ANALISIS KREATIVITAS GURU DALAM PROSES PEMBELAJARAN PADA MATA PELAJARAN IPS DI SMPN 2 KOTO KAMPAR HULU - Deska Ela Sukma; Syakdanur Syakdanur; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the creativity of teachers in the learning process on social studies subjects at SMPN 2 Koto Kampar Hulu. The subjects in this study were 31 students, followed by social studies teachers, supervisors and school principals. SMP Negeri 2 Koto Kampar Hulu. The research data were collected using interview, observation, and documentation techniques. In this study, using qualitative descriptive analysis techniques, with steps starting from data collection, data reduction, data presentation and finally drawing conclusions. Based on the results of the study, it was concluded that the creativity of social studies teachers at SMPN 2 Koto Kampar Hulu had not shown the criteria for creative teachers, especially in relation to the ability of teachers to systematically organize material from easy to difficult, manage classes, prepare learning media and implement various learning methods. The low ability in this case results in a lack of attention and motivation to learn students in the learning process so that it affects student achievement. Therefore, to increase teacher creativity can be done by participating in teacher creativity development training.Key Words: Teacher Creativity, Social Studies Learning